Chemical characteristics of rainwater collected at selected sites around Kuantan - Syakhsiah , Jaafar (2012)
This study was conducted to determine the composition of rainwater at five selected station in the area between Gambang to Kuantan in Pahang, from end of September 2011 until late November 2011. The samples were collected randomly using polyethylene open container and the parameters measured were the anions (F, Cl-, NO3 , p 0, 2-and SO4 2), cations (K, Mg 2 , Na t , Ca 2 , and NH 4 ) and trace metal include Lead(Pb), Cadmium(Cd), Iron(Fe), Manganese(Mn), Copper(Cu), and Chromium(Cr). For the rainwater samples, the ionic species was analyzed using Ion Exchange Chromatography while Atomic Absorption Spectrometer was used to analyzed trace metal species. The pH value of the rainwater were determined. As the result from this study, for station 1 located at Felda Lepar Hilir, the dominant cation was calcium with concentration 1.206±0.11 9mg/L and the dominant anion was nitrate ion with concentration (1 .224±0.304mg/L. The pH obtained at station 1 was 5.5 1±0.562. for Station 2 located at UMP, the dominant cation was calcium with concentration 1 .856±3.092mg/L and the dominant anion was sulphate ion with concentration 1.220±0.632mg/L. The pH obtained for station 2 was 5.34±0.22. For Station 3, the dominant cation was calcium with concentration 0.833±0.467mg1L and the dominant anion was chloride with concentration 0.826±1.233mg/L. The pH obtained for this station was 6.05±0.56. For station 4 located at Kuantan Royal Malaysian Air Force base, the dominant cation was calcium with concentration 1.816±0.767mg/L and the dominant anion was nitrate with concentration 1.692±0.876mg/L. The pH obtained from this sampling site was 6.43±0.33. For the last station which is located at Kuantan city. The dominant cation was calcium with concentration 1.544±0.3 1 lmg/L and the dominant anion was sulphate with concentration 1 .244±0.6O6mgIL. The pH obtained for this sampling site was 6.65±0.04. For the determination of the trace metal species, trace metal species was not detected since the value obtained was below the limit of detection. Hence can be conclude that chemical composition of rainwater depending on the geographical location and main activity of each sampling location. Hence can be conclude that chemical compostion of rainwater is depending on the main activity at the sampling area.